Legal terminology as the basis for the accuracy of legal norms - Teremetskyi, Vladyslav Ivanovych; Lazariev, Viktor Viktorovych; Topchii, Vasyl Vasylovych; Vitiuk, Dariia Liubomyrivna; Roy, Oleh Volodymyrovych (Edelweiss Applied Science and Technology, 2025)
The purpose of the article is to analyze the essence of legal terminology and the peculiarities of its formation, mechanisms of its unification and standardization, as well as to identify the key factors influencing its application. The methodological basis of the work is a set of techniques and methods of scientific cognition: terminological approach, hermeneutic method, method of comparison, method of abstraction, and empirical analysis. The use of these research methods made it possible to carry out a systematic analysis of legal terms and to determine their place in jurisprudence. The authors of the article characterized the essence of legal terminology and the principles of its formation. The authors emphasized that a well-developed conceptual and categorical apparatus is a necessary element of high-quality legislation in the country. It was noted that the meaning of a term should be clearly defined when using legal terminology, because that term may significantly differ in its orientation and scope. The term should also be used depending on legal systems. Particular attention was paid to the comparative analysis of legal terms in different legal systems, which allows for revealing the problems of their translation and adaptation in the international legal space. Several areas can be singled out within the approaches to the formation of legal terminology: own legal terminology, classical legal terminology, and borrowed legal terminology. The regulation of legal terminology requires, first of all, regulating the terminological base on the basis of a preliminary analysis of concepts, their in-depth scientific development, classification and differentiation, and precise definition. Formal certainty allows us to avoid ambiguity, synonymy, duplication, variability, homonymy, and expressive and stylistic tinge of legal terms in regulatory legal acts.